2014
DOI: 10.1007/s11892-014-0494-0
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Endocrine Disruption of Energy Metabolism and Cardiovascular Risk

Abstract: Rates of metabolic and cardiovascular diseases have increased at an astounding rate in recent decades. While poor diet and physical inactivity are central drivers, these lifestyle changes alone fail to fully account for the magnitude and rapidity of the epidemic. Thus, attention has turned to identifying novel risk factors, including the contribution of environmental endocrine disrupting chemicals. Epidemiological and preclinical data support a role for various contaminants in the pathogenesis of diabetes. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
16

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 174 publications
(195 reference statements)
2
51
0
16
Order By: Relevance
“…We also modelled to see whether the associations between housing built year and individual health status would persist after additionally adjusting for environmental chemicals. This is because environmental chemicals have been observed to play a role in human health pathway (Kirkley and Sargis 2014;Shiue and Hristova 2014;Yorita et al 2013), and we hypothesised that environmental chemicals could be confounding the associations between housing age and human health. As expected, those observed significant associations mentioned above all disappeared (data not shown).…”
Section: Housing Built Year and Biomarkersmentioning
confidence: 99%
“…We also modelled to see whether the associations between housing built year and individual health status would persist after additionally adjusting for environmental chemicals. This is because environmental chemicals have been observed to play a role in human health pathway (Kirkley and Sargis 2014;Shiue and Hristova 2014;Yorita et al 2013), and we hypothesised that environmental chemicals could be confounding the associations between housing age and human health. As expected, those observed significant associations mentioned above all disappeared (data not shown).…”
Section: Housing Built Year and Biomarkersmentioning
confidence: 99%
“…Lifestyle factors such as decreased physical activity and energy rich diet, together with a genetic predisposition, are known as main factors in the onset of metabolic dysregulation and metabolic syndrome and related obesity, diabetes, and cardiovascular risks (Kirkley and Sargis, 2014). On the other side, the limited success in reversing such morbidities by focusing solely on nutrition, physical exercise or drug therapies fosters the hypothesis of a significant contribution from environmental chemical factors (Heindel et al, 2015).…”
Section: Potential Long-term Health Risks Of Unregulated Use Of Pestimentioning
confidence: 99%
“…Indeed, multiple chemicals with different half-lives, metabolism, persistence, tissue accumulation and target sensitivities affect many aspects of metabolism (Kirkley and Sargis, 2014). Metabolic disruption is crucial to the effectiveness of prevention plans (cumulative exposure).…”
Section: Hints For Risk Analysis Based On One Healthmentioning
confidence: 99%
“…BPA is widely used over the world in the plastics industry and in the manufacturing of packaging [13], and can be detected in >90% of humans [13]. BPA exposure is associated with obesity, diabetes, disorders of the reproductive and immune systems, oxidative stress and endothelial dysfunction [14,15,16,17,18,19,20]. Recently, Pellegrini et al [21] showed that BPAis able to affect migration in rat vascular smooth muscle cells, especially in female cells.…”
Section: Introductionmentioning
confidence: 99%